Music, imagery training, and sports performance - Kuan, G. (2014)
Imagery is widely used in performance enhancement in sport. Music is also used to enhance sports performance. In this thesis, I examined the role of relaxing and arousing music during imagery on subsequent sports performance in three linked studies. The purpose of Study 1 was to investigate the effects of relaxing and arousing music on physiological indicators of arousal level and subjective psychological perception of arousal during imagery of a sport task. First, appropriate music excerpts were selected with the involvement of professional musicians, sport psychologists, and sport science students. They selected three unfamiliar relaxing music (URM) excerpts, three unfamiliar arousing music (UAM) excerpts, and three familiar arousing music (FAM) excerpts from 90 pre-selected classical music excerpts generated in an initial search for use with imagery. In this study, unfamiliar music excerpts were chosen to minimise the confounding effects of individual past associations which affect arousal level in unpredictable ways. FAM excerpts were added to test the differences between familiar and unfamiliar arousing music. After that, 12 skilled shooters performed shooting imagery while listening to the three preselected music excerpts of each type (URM, UAM, and FAM) each in random order. Using a ProComp+ system and BioGraph Software version 5.0 from Thought TechnologiesTM, I monitored participants` galvanic skin response (GSR), peripheral temperature (PT), electromyogram (EMG), and heart rate (HR) during each type of music, which was played concurrently with imagery. Each participant listened to three classical music excerpts representing each of the three categories (nine pieces in total). Three music excerpts were played in each iv of the three training sessions, with resting levels of physiological measures being recorded before conducting the next imagery session. Between these excerpts, participants rested until normal arousal levels were regained. Results from subjective music ratings, physiological and psychological measures showed UAM was the most arousing and URM was the most relaxing music. In Study 2, I aimed to test whether relaxing, arousing, or no music affected the subjective experience of the imager, and the performance of a dart throwing sport task. Participants in this study were 63 sport science students with intermediate imagery ability, measured by the Sport Imagery Ability Measure (SIAM; Watt, Morris, & Andersen, 2004). Participants were matched into three groups: 1) unfamiliar relaxing music during imagery (URMI), 2) unfamiliar arousing music during imagery (UAMI); and 3) no music during imagery (NMI - control). A pre-test-intervention- post-test design was used with 40 trials of throwing darts at a concentric circles dartboard at pre-test and post-test. The Competitive State Anxiety Inventory-2R (CSAI-2R; Cox, Martens, & Russell, 2003) was administered before the pre-test and after the post-test dart-throwing performance. All participants completed 12 sessions (four weeks) of imagery. In Session 1 and 12, participants` GSR, PT, and HR were measured. Manipulation checks indicated that URMI showed the lowest levels of arousal and arousal level in this condition reduced most from the start to end of sessions. UAMI howed the highest levels of arousal and NMI levels were between those of URMI and UAMI. One-way ANOVA of dart-throwing gain scores revealed that there was a significantly greater gain score for performance for URMi than the other conditions, F (2, 62) = 5.03, p = .01, eta2 = .14. Gain scores were URMI = 37.24 v ± 25.94, UAMI = 17.57 ± 24.30, and NMI = 13.19 ± 28.15. Post Hoc Tukey tests indicated that there was a significant difference in gain scores on dart-throwing performance for URMI versus UAMI, p = .04, and URMI versus NMI, p = .01. However, there was no significant difference between UAMI and NMI, p = .85. In the final study, Study 3, I examined the effects of relaxing and arousing music during imagery on the subsequent performance of high-arousal power and fine-motor skill tasks, and the subjective experience of both relaxing and arousing music during imagery training, using a match-mismatch approach. The study included a pre-test - intervention - post-test design. Participants were semi-professional elite shooters (n = 26) and weightlifters (n = 25). All participants had moderate to high imagery ability measured by the SIAM and had at least two years of competitive experience at State level. In both sports, participants were assigned at random to one of two interventions: unfamiliar relaxing music during imagery (URMI), and unfamiliar arousing music during imagery (UAMI). This produced four conditions: fine motor task (pistol shooting) with either relaxing (URMI; matched) or arousing (UAMI; mismatched) music, and power task (weightlifting) with either relaxing (URMI; mismatched) or arousing (UAMI; matched) music. Shooting performance was measured in a standard 10m air-pistol shooting simulated competition, and weightlifting performance was measured on a simulated competition of a standard Olympic event - Clean and Jerk. All participants completed 12 sessions of imagery over four weeks before the post-test was conducted. In Session 1 and 12, participants` GSR, PT, and HR were measured. The CSAI-2R was administered prior to pre-test and post-test performance. For pistol shooting, results from the independent samples t-test vi showed that differences across type of music used with imagery were significant on the gain-score for competition performance t(24) = 2.71, p = .01, Cohen`s d = 1.06, with a significantly larger increase in performance for URMI than UAMI. For weightlifters, results from the independent samples t-test revealed the differences between conditions were significant in terms of gain-scores for competition performance t(23) = 5.63, p < .001, Cohen`s d = 2.26, with a significantly greater gain score with unfamiliar relaxing music than unfamiliar arousing music. Contrary to previous findings when music was played before or during actual sports tasks, in this study unfamiliar relaxing music facilitated imagery of both fine-motor and power sports tasks, suggesting that relaxation plays a role in the imagery of sports skills. If this finding is replicated for the use of music with imagery across other strength and power tasks that are usually enhanced by arousing music prior to or during actual performance (Karageorghis et al., 2009; Simpson & Karageorghis, 2006), it has important implications for the use of particular types of music with imagery, and supports the proposition that relaxation is beneficial for imagery.